Continuing versus stopping prestroke antihypertensive therapy in acute intracerebral hemorrhage: a subgroup analysis of the efficacy of nitric oxide in stroke trial - Krishnan, Kailash; Scutt, Polly; Woodhouse, Lisa J.; Adami, Alessandro; Becker, Jennifer L.; Cala, Lesley A.; Casado, Ana M.; Chen, Christopher; Dineen, Robert A.; Gommans, John; Koumellis, Panos; Christensen, Hanna; et al. (W.B. Saunders, 2016)
Background and purpose: More than 50% of patients with acute intracerebral haemorrhage (ICH) are taking antihypertensive drugs before ictus. Although antihypertensive therapy should be given long term for secondary prevention, whether to continue or stop such treatment during the acute phase of ICH remains unclear, a question that was addressed in the Efficacy of Nitric Oxide in Stroke (ENOS) trial. Methods: ENOS was an international multicenter, prospective, randomized, blinded endpoint trial. Among 629 patients with ICH and systolic blood pressure between 140 and 220 mmHg, 246 patients who were taking antihypertensive drugs were assigned to continue (n = 119) or to stop (n = 127) taking drugs temporarily for 7 days. The primary outcome was the modified Rankin Score at 90 days. Secondary outcomes included death, length of stay in hospital, discharge destination, activities of daily living, mood, cognition, and quality of life. Results: Blood pressure level (baseline 171/92 mmHg) fell in both groups but was significantly lower at 7 days in those patients assigned to continue antihypertensive drugs (difference 9.4/3.5 mmHg, P < .01). At 90 days, the primary outcome did not differ between the groups; the adjusted common odds ratio (OR) for worse outcome with continue versus stop drugs was .92 (95% confidence interval, .45- 1.89; P = .83). There was no difference between the treatment groups for any secondary outcome measure, or rates of death or serious adverse events. Conclusions: Among patients with acute ICH, immediate continuation of antihypertensive drugs during the first week did not reduce death or major disability in comparison to stopping treatment temporarily.